Research on the Detection Method of Martian Atmospheric Temperature and Pressure Profile Based on Laser Occultation Technology - Ye Liu; Wei Kong; Xue Shen; Tao Chen; Genghua Huang (Remote Sensing)
As an important target of space exploration, Mars has attracted a lot of attention due to its unique geographical and atmospheric conditions. The detection of the vertical profiles of Mars atmospheric parameters provides deeper insights into the structure and composition of the Martian atmosphere. Meanwhile, it holds significant importance for the design and execution of Mars exploration missions. This paper presents a detection method for the Martian atmosphere utilizing laser occultation technology based on a network of high-orbit and low-orbit satellites around Mars. The measurement principle of Mars laser occultation is first introduced, which is that the atmospheric temperature and pressure are measured by analyzing the absorption spectrum characteristics of infrared carbon dioxide. Then, a detailed simulation process is described, including the establishment and validation of both the radiation intensity calculation model for laser occultation signals and the method for retrieving atmospheric parameters. A set of satellite payload parameters is also designed. The simulation results reveal that this method can accurately measure temperature and pressure at a vertical resolution of 100 m from 5 km to 50 km altitude of the Martian atmosphere with deviations of 0.43 K and 1.06%, respectively. It is indicated that the proposed laser occultation method can achieve effective detection of temperature and pressure and provide a promising approach for high vertical resolution profile detection of the Martian atmosphere in the future.